'Traveling nutrients': how students use metaphorical language to describe digestion and nutritional uptake. Issue 8 (23rd May 2020) - Jahic Pettersson, Alma; Danielsson, Kristina; Rundgren, Carl-Johan
ABSTRACT: Previous research suggests that students use metaphors when asked to explain digestive processes and nutritional uptake. In this paper, we describe the results of a study designed to gain a deeper understanding of how metaphors and anthropomorphisms are used by students when describing such processes. We applied analyses based on the systemic-functional grammar framework to 123 student responses to a question about nutrition on a Swedish national test in biology in order to identify, describe and analyse how students use metaphors and to understand the linguistic structure of those metaphors. We also considered how the metaphors are linked to metaphor systems and anthropomorphisms, thereby gaining a deeper understanding of the role of metaphors in this area. The results of our analyses provide important insights into how students understand digestion and nutrition and could provide the basis for improved teaching materials and methods for these important topics.